PENGUATAN PEMBELAJARAN KEWIRAUSAHAAN BERBASIS PROYEK SMK WIKRAMA BOGOR MENGGUNAKAN HUMAN-CENTERED DESIGN DAN TEKNOLOGI 3D PRINTING - Noviyanti, Anastasia; Prakasa, Danang Yudha; Saldi, Zaki Saptari; Sembadha, Syntia Sukma; Santana, Fillberto Canvin (Universitas Trisakti, 2024)
Entrepreneurship is a career choice for graduates of Vocational High Schools. One method that can be used to provide entrepreneurial knowledge and skills is project-based learning (PBL). In this implementation, PBL on entrepreneurship challenges bridging the material and teaching atmosphere with value creation and user orientation principles. To answer this challenge, training on product development using human-centered design and 3D printing technology within the PBL framework has been provided to Wikrama Vocational School Bogor as partners in the community service program. This activity aims to provide essential teacher knowledge about human-centered design-based entrepreneurship and implement this concept in students' PBL plans, providing basic knowledge and skills for teachers about 3D printing to enrich students' PBL, raising teacher empathy in PBL, and strengthening teachers' knowledge about creativity and innovation. The application of PBL has produced a prototype of the product design process. Evaluation of the activities shows the effectiveness of the training in increasing teachers' understanding of entrepreneurship, human-centered design, empathy processes, and 3D printing, which is shown in the increase in the average pre-test and post-test scores from 62% to 84%. Furthermore, teachers can apply the PBL framework to strengthen student learning.